Control de Ingresos en la Compañía de Transporte Mixto San Agustín de Jujan CTMSAJCOM S.A. - Bravo Espín, María Cristina (2018)
In Ecuador, any company regardless of its size or economic activity must keep an accounting control of their financial operations, accounting in companies is feeds information that is processed. The present case study, is given in the company TRANSPORT COMPANY MIXTO SAN AGUSTIN DE JUJAN CTMSAJCOM S.A., located in the Tres Postes Campus S / N of the Alfredo Baquerizo Moreno parish, in the province of Guayas, a company that dedicates to the regular mixed transport service, which analyzes the lack of control that there is income and that it carries with it erroneous information for the elaboration of financial statements. With the collaboration of Mr. Manager of the company and through the technique of Interview with the same, also applying the inductive method of investigation, is intended find the causes that cause that an adequate control of the income is not carried out, as well such as expenditures, all this causes that the information obtained to record the The daily transactions of the company in its accounting system are not adequate, causing that at the moment of elaborating the financial statements these contain information not reliable and the decisions that are made are not correct. This research presents as objective to know the management that is carried out time to record the income of the company MIXED TRANSPORTATION COMPANY SAN AGUSTIN DE JUJAN CTMSAJCOM S.A., since the invoice is issued and the collection of the same. In order to carry out the present work, the provisions of the investigation of the Accounting, Audit and Finance career of the Faculty of Administration, Finance and IT, Accounting information management